Brucella endocarditis in a non-endemic area presenting as pyrexia of unknown origin. (19th September 2014) - Manade, Vivek Vilas; Kakrani, Arjun; Gadage, Siddharth Narayan; Misra, Rabindra
Abstract : A 67-year-old man with type 2 diabetes mellitus and hypertension since 7 years presented with a 3-month history of low-grade fever and malaise. Cardiac auscultation revealed the presence of an ejection systolic murmur in the primary aortic area. Most of the investigations for febrile illness were reported normal. His two-dimensional (2D) echocardiogram revealed a calcified aortic valve with mild aortic stenosis. In view of the prolonged fever and calcified aortic valve with mild aortic stenosis, a transoesophageal echocardiogram was performed, which showed small vegetation noted on right coronary cusp about 2.2 mm with free independent mobility. Blood culture was positive for Brucella spp from all the three venepuncture sites. Medical therapy for brucellosis was given with ciprofloxacin, doxycycline, co-trimoxazole and streptomycin, resulting in complete recovery. Brucella endocarditis is a rare, mostly ignored and missed clinical infection. It requires a high index of clinical suspicion for prompt diagnosis and treatment.